Text and performance: Tayyartu, “repetition,” in a Mīs Pî-type incantation and an emesal prayer - Gabbay, Uri (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2017)
The following examines the Akkadian scribal annotation tayyartu, “return,” demonstrating that it refers to a repetitive section of a text that was not copied by the scribe. Editions of two texts where this annotation occurs, a Mīs Pî-type incantation and an Emesal prayer, are included. In addition, the phenomenon of repetition and abbreviation in incantations and Emesal prayers is briefly discussed.